Current advances in the molecular regulation of abiotic stress tolerance in sorghum via transcriptomic, proteomic, and metabolomic approaches - Tu, Min; Du, Canghao; Yu, Boju; Wang, Guoli; Deng, Yanbin; Wang, Yuesheng; Chen, Mingjie; Chang, Junli; Yang, Guangxiao; He, Guangyuan; Xiong, Zhiyong; Li, Yin (Frontiers in Plant Science, 2023)
Sorghum (Sorghum bicolor L. Moench) is a monocot C4 crop, an important staple crop for many countries in the arid and semi-arid areas in the world. Sorghum has outstanding tolerance and adaptability to a variety of abiotic stresses, including drought, salt and alkaline, and heavy metal stresses, thus representing a valuable research material for understanding the molecular mechanisms of crop stress tolerance and mining new genes for the genetic improvement of abiotic stress tolerance. In the present study, we compile the recent research advances achieved by using physiological, transcriptome and proteome approaches, discusses the similarities and differences of the sorghum responses to different stresses, and summarizes the candidate genes involved in the process of response and regulation of the stresses. More importantly, we exemplify the differences between combined stresses and a single stress, emphasizing the necessity to strengthen the molecular responses and mechanisms of combination of abiotic stresses, as combined stresses are of more practical significance. Our review lays a foundation for the functional studies of stress-tolerance-related genes and provides new insights into the molecular breeding of stress-tolerant sorghum genotypes and lists a catalog of candidate genes for improving the stress tolerance for other monocot crops, such as maize, rice, and sugarcane.